Digital Leadership in Education: A Bibliometric Analysis - Mardalena, Mardalena; Sarinah, Sarinah; Elfisa, Yesi; Basroh, Muhammad Ali; Pratiwi, Anggia; Ningsih, Retno Wahyu (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
A crucial skill for guiding educational institutions through technological change is digital leadership. To improve strategic educational reform, it is essential to comprehend how academic research on digital leadership has changed as educational institutions and schools around the world embrace digital ecosystems. Using information from the Scopus Core Collection, this study performs a bibliometric analysis of studies on digital leadership in education conducted between 2010 and 2025. To find publication trends, prominent authors, nations, and topic groups, analyses were conducted using VOSviewer and Biblioshiny for R. A total of 1,174 documents with 3,217 authors were gathered from 556 sources. There is a strong and expanding scholarly interest, as evidenced by the publications' 28.01% annual growth rate. The average number of citations per paper was 14.61, the number of co-authors per publication was 3.18, and the international collaboration rate was 23.85%. Journal articles made up the majority of the documents (773), followed by conference papers (146) and book chapters (170). Growing clusters centered on digital transformation, educational innovation, teacher digital competency, and AI-driven leadership were revealed by the co-occurrence analysis. The results show that, with an emphasis on strategic change, equity, and digital ethics, research on digital leadership in education has expanded rapidly, especially since 2019. In order to assist in forming future educational leadership scholarship, this study offers the first comprehensive bibliometric mapping of digital leadership in education, outlining its intellectual structure, thematic evolution, and research boundaries.